EDUKASI SEJAK DINI REMAJA SEHAT BEBAS ANEMIA - Rouzatun Nisa; Zaitun Zaitun; Finaul Asyura; Silmi Kaffah; Kesumawati Kesumawati (Universitas Ubudiyah Indonesia, 2025)
Abstract Anemia is a global health problem that occurs in many adolescents, especially adolescent girls. According to the World Health Organization (WHO), anemia is defined as a condition in which the hemoglobin (Hb) level in the blood is below normal limits. the prevalence of anemia among adolescents remains high at 32% according to Riskesdas 2018. Lack of knowledge is one of the contributing factors to anemia among adolescents. This community service activity aimed to improve adolescents’ knowledge about anemia through health education. The method used was an educative-participatory approach with a one group pretest-posttest design. The activity using interactive lectures supported by PowerPoint media. Evaluation was conducted using a knowledge questionnaire before and after the education session. The results showed a significant increase in the average knowledge score from 4.10 to 9.28 with a p-value of 0.000. Health education effectively improved adolescents’ understanding of anemia. This program is expected to encourage preventive behaviors to reduce anemia among adolescents and support the development of a healthy and productive young generation. Keywords: Education, Adolescents, Anemia, Hemoglobin